Drivers of burrow symbiont distribution in a softsediment system: host abundance or burrow trophic environment? - Wright, Amy G (Department of Biological Sciences, 2014)
The Langebaan Lagoon sandflats are dominated by the burrowing activities of thalassinid shrimps. Their burrows are home to various burrow symbionts including a commensal shrimp (Betaeus jucundus), a six-legged crab (Spiroplax spiralis) and a scaleworm (Antinoe lactea). Little work has been conducted on these burrow symbionts, and the mechanisms influencing their abundance and distribution are unknown. To test whether host abundance or the burrow trophic environment (i.e. food availability) is the dominant force shaping patterns of burrow symbiont distribution, samples of host and symbiont abundances as well as chlorophyll-a and extracellular polymeric substance (EPS) measurements were taken from three sites in Langebaan Lagoon over spring and autumn. Clear signals emerged in contradiction of the hypothesis that burrow symbiont abundances peak in areas associated with high abundances of hosts. Host abundances peaked at Bottelary (10.18 counts/site ± 1.02 SE), a site where recreational activities and thalassinid shrimp bait collection are prohibited. In contrast, peak B. jucundus abundance (6.56 counts/site ± 0.37 SE) occurred at Oesterval during September – the muddy sediment of the site resulted in high sedimentary food retention and the September spring phytoplankton bloom resulted in peak chlorophylla (234.12 mg chl-a/g sediment ± 42.74 SE) and EPS (0.13 mg EPS/g sediment ± 0.008 SE) concentrations. Regression analyses confirmed that food availability was the best explanation of the patterns observed in B. jucundus distributions, over and above that of host distributions. S. spiralis and A. lactea did not show this pattern, the result of the low counts of these species in the collected samples or their reliance on food sources different to those depended on by B. jucundus. These results are of consequence in changing the way we think about symbiont distributions relative to that of the hosts, in that the two may not be linked directly, but rather influenced by larger scale trophic changes such as the availability of food within the burrow.